2020
DOI: 10.3390/nu12061608
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Sulforaphane and Fernblock® XP Improves Individual Beneficial Effects in Normal and Neoplastic Human Skin Cell Lines

Abstract: Plenty of evidence supports the health effects exerted by dietary supplements containing phytochemicals, but the actual efficacy and safety of their combinations have been seldom experimentally evaluated. On this basis, we investigated in vitro the antioxidant/antineoplastic efficacy and anti-aging activity of a dietary supplement containing sulforaphane (SFN), a sulfur-isothiocyanate present in broccoli, combined with the patented extract Fernblock® XP (FB), obtained from the tropical fern Polypodium leucotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Treatment of keratinocyte cell line NCTC2544 with SFN (10 µM) combined with the Fernblock® XP (1 and 2 mg/ml), obtained from the tropical fern Phlebodium aureum (L.) J.Sm., substantially suppressed the production of MMP-1, MMP-3 and IL-1 in association with a decrease in ROS production. The SFN (5 and 10 µM) and Fernblock® XP (1 mg/ml) combination also showed inhibitory effects on melanoma cell growth and migration in vitro in association with the ability to inhibit the inflammatory microenvironment and neo-angiogenesis ( Serini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of keratinocyte cell line NCTC2544 with SFN (10 µM) combined with the Fernblock® XP (1 and 2 mg/ml), obtained from the tropical fern Phlebodium aureum (L.) J.Sm., substantially suppressed the production of MMP-1, MMP-3 and IL-1 in association with a decrease in ROS production. The SFN (5 and 10 µM) and Fernblock® XP (1 mg/ml) combination also showed inhibitory effects on melanoma cell growth and migration in vitro in association with the ability to inhibit the inflammatory microenvironment and neo-angiogenesis ( Serini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous data also similarly reported that SFN is able to suppress MMP‐9 expression in MCF‐7 cells 40 and was found to inhibit MMP‐1, −3 and −13 expressions in IL‐1 and TNF‐ α‐stimulated chondrocytes 41 . A recent study on skin ageing suggested that SFN combined with a Polypodium leucotomos commercial extract inhibited the MMP‐1 and MMP‐3 productions in both normal keratinocytes and melanoma cells, significantly 42 . Even though, the aqueous extract of THS is lack of several organic soluble toxic compounds, numerous studies as well as the present study showed that water‐soluble toxic chemicals are able to induce cytotoxicity particularly via oxidative and inflammatory damage.…”
Section: Discussionmentioning
confidence: 62%
“…In 2021, Serini et al [ 71 ] conducted an in vitro study in which they assessed the antioxidant, antineoplastic, and antiaging activity of a dietary supplement containing PLE combined with sulforaphane (SFN), a sulfur-isothiocyanate present in broccoli. The PLE/SFN combination inhibited melanoma cell migration in vitro as well as MMP production, inflammasome activation, and IL-1β secretion more efficiently than individually.…”
Section: Clinical Use In Photodamage Preventionmentioning
confidence: 99%